“Evaluación de tres bioestimulantes en la producción de dos variedades de acelga (Beta vulgaris)” - Herrera Jácome, Jahelly Elizabeth (2023)
The research was carried out in El Carmen parish, La Maná canton, Cotopaxi province. The following objectives were set: to valuate three biostimulants in the production of two varieties of chard (Beta vulgaris), to identify the best production in the cultivation of chard (Beta vulgaris), to establish the influence of biostimulants on the vegetative development of chard (Beta vulgaris) crops, to carry out an economic analysis of the treatments on the Abejo and Fordhook giant variety of chard. The evaluated variables were: leaf length (cm), leaf width (cm), number of leaves at harvest (unit), weight per plant (g), net weight of the plot (g), and yield (kg/ha). The best results were obtained with T7 (amino acids + Fordhook giant), so obtaining a value of 43.58 cm in leaf length, weight per plant 403.63 grams, net weight of the plot 9687 grams, and T6 (amino acids + Abejo) leaf width with a value of 15.09 cm, number of leaves at harvest of 7.33. Finally, in yield, a value of 15376.19 (kg/ha) was obtained, giving T7 (amino acids + Fordhook giant) as the best treatment and a cost/benefit of $6.26.